Sweat equity : inside the new economy of mind and body - Kelly, Jason, 1973- (Bloomberg Press, 2016)
"Go inside the trend that spawned a multi-billion dollar industry for the top five percent Sweat Equity goes inside the multibillion dollar trend toward endurance sports and fitness to discover who's driving it, who's paying for it, and who's profiting. Bloomberg's Jason Kelly, author of The New Tycoons, profiles the participants, entrepreneurs, and investors at the center of this movement, exploring this phenomenon in which a surge of people--led by the most affluent--are becoming increasingly obsessed with looking and feeling better. Through in-depth looks inside companies and events from New York Road Runners to Tough Mudder and Ironman, Kelly profiles the companies and people aiming to meet the demands of these consumers, and the traits and strategies that made them so successful. In a modern world filled with anxiety, pressure, and competition, people are spending more time and money than ever before to soothe their minds and tone their bodies, sometimes pushing themselves to the most extreme limits. Even as obesity rates hit an all-time high, the most financially successful among us are collectively spending billions each year on apparel, gear, and entry fees. Sweat Equity charts the rise of the movement, through the eyes of competitors and the companies that serve them. Through conversations with businesspeople, many driven by their own fitness obsessions, and first-hand accounts of the sports themselves, Kelly delves into how the movement is taking shape. Understand the social science, physics, and economics of our desire to pursue activities like endurance sports and yoga Get to know the endurance business's target demographics Learn how distance running--once a fringe hobby--became a multibillion dollar enterprise fueled by private equity Understand how different generations pursue fitness and how fast-growing companies sell to them The opportunity to run, swim, and crawl in the mud is resonating with more and more of us, as sports once considered extreme become mainstream. As Baby Boomers seek to stay fit and Millennials search for meaning in a hyperconnected world, the demand for the race bib is outstripping supply, even as the cost to participate escalates. Sweat Equity, through the stories of men and women inside the most influential races and companies, goes to the heart of the movement where mind, body, and big money collide"--